A low cost and rapid analytical technique for direct spectrophotometric determination of chromium in V–Cr–Ti alloys without a chromogenic agent. Issue 30 (20th July 2017) - Tian, L. F.; Zou, D. S.; Dai, Y. C.; Wang, L. L.; Gao, W.
Abstract : A simple, rapid and accurate spectrophotometric method was developed for the determination of chromium in V–Cr–Ti ternary alloy without any prior separation and chromogenic agent. Abstract : Quantification of chromium in V–Cr–Ti ternary alloys, used as candidate structural materials for fusion reactors, is essential in view of its significant effect on the properties of these vanadium-based alloys. Various methods have already been used for the determination of chromium in common alloys, but most of these methods are based on complicated and expensive instruments or suffer from the serious matrix interference of vanadium. In this study, a simple, rapid and accurate spectrophotometric method was developed for the determination of chromium in V–Cr–Ti alloys without any prior separation and chromogenic agent. The alloy samples were dissolved in diluted sulphuric acid and concentrated nitric acid, and chromium was oxidized with persulphate in the presence of Ag(i ) ions as a catalyst. After alkalization of the solution with sodium hydrate, greenish-yellow coloured chromate (CrO4 2− ) ions were formed in the alkaline solution and had a maximum absorption peak at 374 nm. Beer's law was obeyed in the range of 0.15–12.0 μg mL −1 Cr(vi ) at 374 nm and the molar absorptivity was 4.8 × 10 3 L mol −1 cm −1 . All the variables were studied in order to optimize the analytical conditions. Vanadium and titanium seriously interfered with the determination of Cr(vi ) and their interference can be eliminated by addition of ammonium tartrate. The proposed method is simple, fast, accurate and of low cost, and has been satisfactorily used for the determination of chromium in V–Cr–Ti alloys. The results are in good agreement with data given by inductively coupled plasma optical emission spectrometry (ICP-OES) and the relative standard deviation is found to be lower than 0.4%.